Effect of some antineoplasics on metabolic heme pathway - Wainstok De Calmanovici, R. (1988)
1. 1. The porphyrinogenic ability of several antineoplasics used in the therapy of the different cancers was evaluated. The action of cyclophosphamide, busulfan and 5-fluorouracil on the amount and nature of the accumulated hepatic porphyrins and on the activity of δ-aminolaevulinate synthase(ALA-S). were estimated at different doses and times of drug treatment in 17-day-old chick embryos. 2. 2. It was observed that cyclophosphamide produces a significant increase in the accumulation of hepatic porphyrins at different doses as well as in the activity of the ALA-S, at all the incubation times. Cyclophosphamide alters the pattern of porphyrins accumulated in the liver, where a coproporphyrin: protoporphyrin ratio higher than in the controls can be observed. 3. 3. Busulfan increased the hepatic porphyrins accumulated in the liver but to a lesser degree than cyclophosphamide. 4. 4. 5-Fluorouracil did not modify the hepatic porphyrin content when it was administered at doses up to 40 mg/embryo. 5. 5. When the embryos were injected with busulfan or 5-fluorouracil no significant differences were observed in the activity of ALA-S up to 11 hr of incubation. 6. 6. These results indicate that cyclophosphamide has a remarkable porphyrinogenic capacity in chick embryo while busulfan. notwithstancling the fact that it alters the haem pathway, it does so to a degree that does not impair the regulation of ALA-S activity. Fluorouracil seems to be non porphyrinogenic in this system, up to 40 mg/embryo. © 1988.